Pengaruh Brand Equity dan Customer Satisfaction terhadap Repurchase Intention Melalui Brand Loyalty Sebagai Variabel Intervening di D’konkrit Coffee & Food - Jodi Safutra; Henny Welsa; Nonik Kusuma Ningrum (Universitas Batanghari, 2023)
This study aims to determine the effect of Brand Equity (X1), Customer Satisfaction (X2), on Repurchase Intention (Y) through Brand Loyalty (Z) as an intervening variable in D'Konkrit Coffee & Food. This type of research is quantitative research by taking samples from 150 customers of d'concrete coffee & food who have made purchases or visited d'konkrit coffee & food as research subjects. Sampling used purposive sampling technique, and data collection was carried out by survey method by distributing questionnaires. The data was processed using the PLS-SEM (Structural Equation Model) method, and the Smart-PLS software statistics by performing a data quality test, classical assumption test, multiple regression test, t test and coefficient of determination test. Based on the test results in this research, it shows that the 5 hypotheses in this study are supported. From these results, it is concluded that if brand equity increases, brand loyalty also increases. Furthermore, it was found that if customer satisfaction increased then brand loyalty also increased. The results also show that if brand equity increases, it can increase repurchase intention. It was also found that if customer satisfaction increases, it can increase repurchase intention and finally it was found that if brand loyalty increases, repurchase intention also increases.